The Quantitative Genetics of Good Genes: Fitness, Male Display, and Female Preference - Delcourt, Matthieu (Université d'Ottawa / University of Ottawa, 2011)
The ultimate goal of my thesis is to develop a better understanding of the contribution of indirect benefits (i.e. good genes) to the evolution of female mate preferences. It is genetic variance in, and genetic correlations (covariances) among, male sexual displays, female preferences for them, and fitness that in part determine the degree to which females preferring certain male displays over others will gain an indirect benefit by having higher fitness offspring. Recent advances in quantitative genetic theory provide the mathematical means for quantifying the strength of indirect selection for female mate preferences (Kirkpatrick and Hall 2004), at least under certain conditions, but there are few empirical systems for which such data exist (Brooks and Endler 2001; Qvarnström et al. 2006). I have undertaken a classic half-sibling breeding design with the ultimate goal of estimating the specific parameters of this model in a population of the Australian fruit fly Drosophila serrata. The breeding design was performed across two environments - one to which the population was well adapted and a novel environment to which it was not - thereby also providing insight into genotype-by-environment interactions for this suite of traits and their effects on good genes indirect benefits in a novel environment. General insight is also gained into the genetic covariance of male and female fitness and the prevalence of intralocus sexual conflict, the quantitative genetic basis of female mate preferences for multiple male traits, the condition-dependence of these traits, and the genetic association between sexual displays and fitness when mutation-selection balance is inferred. My results advocate caution in the application of existing theory to quantify the strength of indirect selection, suggesting that a good genes process may be fundamentally different when the exaggeration of sexual displays is eventually halted and an equilibrium is reached between opposing selection.
Keywords: evolution; sexual selection; good genes; quantitative genetics; G matrix; pleiotropy; Drosophila serrata; female preference; male display; condition-dependence; evolutionary limit; sexual conflict